INFLUENCE OF YEAR AND ATONIK APPLICATION ON VARIABILITY OF SUGAR BEET ROOT YIELD AND DIGESTION - I ČERNÝ; P ONDRIŠÍK (Journal of Central European Agriculture, 2004)
In 1998 and 1999 the effect of weather conditions and different doses of Atonik application on sugar beet root yield and digestion (cultivar Ranger) were studied in the field trial. The trial results confirmed statistically high significant effect of trial year weather conditions on above mentioned parameters. Comparing received results in the year 1998 to results in 1999 we found out lower root yield (- 7,6 t.ha-1) and digestion (- 0,2 t.ha-1) comparing with year 1999. We found out a significant effect of Atonik on root yield (+6,73 t.ha-1, rel.12,56 %) and digestion (+ 0,6 °S,rel. 3,71 %) on the variant C (Atonik treatment) comparing to values of control variant. In general we can evaluate the effect of Atonik application as high significant.